HEALTHCARE WASTE MANAGEMENT (HCWM) IN PAKISTAN: CURRENT SITUATION AND TRAINING OPTIONS - Kumar, Ramesh; Khan, Ejaz Ahmad; Ahmed, Jamil; Khan, Zulifiqar; Magan, Mohamed; Nousheen, Nousheen; Mughal, Muhammad Ibrahim (Journal of Ayub Medical College Abbottabad, 2010)
Background: Hospitals in Pakistan produce about 250,000 tons of waste per year. Hospital waste has been reported to be poorly handled and managed by the hospital staff and administration respectively. This leads to environmental and health consequences within hospitals as well as to outside population. Our study aimed to describe the qualitative results of observations of ten large private and public hospitals in the cities of Rawalpindi and Islamabad Pakistan. Methods: The qualitative data was obtained through direct and indirect observations on hospital staff including doctors, nurses, sweepers and persons in administration and the way they handled the waste. Also direct observations of the hospitals premises inside and outside were made and noted. We also describe the process of involving the hospital staff for trainings. Results: Our results showed that almost all of the hospitals did not have practice of HCWM on their priority. Segregation, handling, storage, transportation and disposal of waste were below WHO and Pakistan bio-safety rules 2005 standards. The ten hospitals did not have HCWM rules and regulations in place hence the staff do not follow the best practices in this regard which causes numerous health and environmental consequences not only within the catchment area but also to patients and staff. Conclusions: Our study highlights the lack of HCWM practices within the ten public and private hospitals in two major cities in Pakistan. There is need of trainings of hospital staff in Pakistan. We also found that such trainings are highly feasible if accompanied with incentives to participants. Keywords: Hospital, Management, Observation, Segregation, Training, Waste